Nanogap Engineered Plasmon‐Enhancement in Photocatalytic Solar Hydrogen Conversion. Issue 14 (6th August 2015) - Chen, Jie; Dong, Chung‐Li; Du, Yuanchang; Zhao, Daming; Shen, Shaohua
<x xml:space="preserve">Abstract</x> Graphitic carbon nitride modified with plasmonic Ag@SiO2 core–shell nanoparticles (g‐C3N4/Ag@SiO2) are proposed for enhanced photocatalytic solar hydrogen evolution under visible light. Nanosized gaps between the plasmonic Ag nanoparticles (NPs) and g‐C3N4 are created and precisely modulated to be 8, 12, 17, and 21 nm by coating SiO2 shells on the Ag NPs. The optimized photocatalytic hydrogen production activity for g‐C3N4/Ag@SiO2 is achieved with a nanogap of 12 nm (11.4 μmol h−1) to be more than twice as high as that of pure g‐C3N4 (5.6 μmol h−1). The plasmon resonance energy transfer (PRET) effect of Ag NPs is innovatively proved from a physical view on polymer semiconductors for photoredox catalysis. The PRET effect favors the charge carrier separation by inducing electron–hole pairs efficiently formed in the near‐surface region of g‐C3N4. Furthermore, via engineering the width of the nanogap, the PRET and energy‐loss Förster resonance energy transfer processes are perfectly balanced, resulting in considerable enhancement of photocatalytic hydrogen production activity over the g‐C3N4/Ag@SiO2 plasmonic photocatalyst.